COVID-19 experiences of social isolation and loneliness among older adults in Africa: a scoping review - Isaac Akinkunmi Adedeji; Andrew Wister; Andrew Wister; John Pickering (Frontiers Media S.A., 2023)
ObjectiveSocial isolation and loneliness (SI/L) are considered critical public health issues. The primary objective of this scoping review is to document the experience of SI/L among older adults in Africa during the COVID-19 pandemic, given research gaps in this area. We identified the reasons for SI/L, the effects of SI/L, SI/L coping strategies, and research and policy gaps in SI/L experiences among older adults in Africa during COVID-19.MethodsSix databases (PubMed, Scopus, CINAHL, APA PsycINFO, Web of Science, and Ageline) were used to identify studies reporting the experiences of SI/L among older adults in Africa during the COVID-19 lockdown. We adopted the Joanna Briggs Institute (JBI) methodology and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR).ResultsSocial isolation and loneliness due to COVID-19 in Africa affected older adults' mental, communal, spiritual, financial, and physical health. The use of technology was vital, as was the role of social networks within the family, community, religious groups, and government. Methodological challenges include the risk of selective survival bias, sampling biases, and limited inductive value due to context. Also, lack of large-scale mixed methods longitudinal studies to capture the experiences of older adults during COVID-19. There were essential policy gaps for African mental health support services, media programs, and community care service integration targeting older adults in the era of the COVID-19 lockdown.DiscussionLike in other countries, COVID-19 lockdown policies and the lockdown restrictions primarily caused the experience of SI/L among older adults in Africa. In African countries, they resulted in a severance of older adults from the cultural structure of care for older adults and their familial support systems. Weak government intervention, personal situations, challenges regarding technology, and detachment from daily activities, disproportionately affected older adults in Africa.